Malaysian public university learning environments: assessing conduciveness through ICT affordances - Jamian, Magdalina; Ab. Jalil, Habibah; Krauss, Steven Eric (Elsevier, 2012)
There is a continuous struggle on understanding learning settings, particularly with ICT integrations. This paper aims to illuminate an alternative means of understanding virtual learning environment which is through affordances (perception-action coupling). Qualitative inquiry was implemented in gathering participants’ experiences and perceptions regarding ICT integration in teaching practices through focus group discussion and semi-structured interviews. This study shows that preferences of ICT integration in learning environment are closely related to ICT affordances. Understanding of ICT affordances is important in order to assessing conduciveness of learning environments with the ICT integrations.